2015
DOI: 10.1016/j.jallcom.2014.12.260
|View full text |Cite
|
Sign up to set email alerts
|

Metal hydrides based high energy density thermal battery

Abstract: a b s t r a c tA concept of thermal battery based on advanced metal hydrides was studied for heating and cooling of cabins in electric vehicles. The system utilized a pair of thermodynamically matched metal hydrides as energy storage media. The pair of hydrides that was identified and developed was: (1) catalyzed MgH 2 as the high temperature hydride material, due to its high energy density and enhanced kinetics; and (2) TiV 0.62 Mn 1.5 alloy as the matching low temperature hydride. Further, a proof-of-concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Some work was presented in literature concerning coupled metal hydride reactions. Fang et al [33] investigated coupled catalyzed MgH 2 -TiV 0.62 Mn 1.5 for heating and cooling of cabins in electric vehicles. Some boundary conditions differ to the presented study (regeneration temperature level of 270°C, material partly combined with expanded natural graphite, ambient temperature of 20°C) which limits comparability.…”
Section: Discussionmentioning
confidence: 99%
“…Some work was presented in literature concerning coupled metal hydride reactions. Fang et al [33] investigated coupled catalyzed MgH 2 -TiV 0.62 Mn 1.5 for heating and cooling of cabins in electric vehicles. Some boundary conditions differ to the presented study (regeneration temperature level of 270°C, material partly combined with expanded natural graphite, ambient temperature of 20°C) which limits comparability.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium hydride is considered a prime candidate material for hydrogen storage and thermal energy storage owing to its high hydrogen storage capacity (7.76 wt %), good reversibility, and low cost. However, there are two major impediments that have prevented the practical use of MgH 2 despite a huge amount of research that has been reported around the globe. One of the issues is that MgH 2 suffers from poor kinetics during hydrogen absorption and desorption reactions.…”
Section: Introductionmentioning
confidence: 99%
“…A thermal battery concept by exploiting advanced metal hydrides was introduced for vehicle cabin cooling and heating. The idea of having higher energy density was based on the differences occurring in hydrogen equilibrium pressures [118]. The working hydrides have matching thermodynamic properties, consisting of MgH2 (high temperature hydride) and TiMnV (low temperature hydride).…”
Section: B Thermal Energy Buffering and Heat Exchangersmentioning
confidence: 99%